Reversible, High-Affinity Surface Capturing of Proteins Directed by Supramolecular Assembly - Di Palma, Giuseppe; Kotowska, Anna; Hart, Lewis R.; Scurr, David J.; Rawson, Frankie J.; Tommasone, Stefano; Mendes, Paula M. (American Chemical Society, 2019)
The ability to design surfaces with reversible, high-affinity protein binding sites represents a significant step forward in the advancement of analytical methods for diverse biochemical and biomedical applications. Herein, we report a dynamic supramolecular strategy to directly assemble proteins on surfaces based on multivalent host–guest interactions. The host–guest interactions are achieved by one-step nanofabrication of a well-oriented β-cyclodextrin host-derived self-assembled monolayer on gold (β-CD-SAM) that forms specific inclusion complexes with hydrophobic amino acids located on the surface of the protein. Cytochrome c, insulin, α-chymotrypsin, and RNase A are used as model guest proteins. Surface plasmon resonance and static time-of-flight secondary ion mass spectrometry studies demonstrate that all four proteins interact with the β-CD-SAM in a specific manner via the hydrophobic amino acids on the surface of the protein. The β-CD-SAMs bind the proteins with high nanomolar to single-digit micromolar dissociation constants (KD). Importantly, while the proteins can be captured with high affinity, their release from the surface can be achieved under very mild conditions. Our results expose the great advantages of using a supramolecular approach for controlling protein immobilization, in which the strategy described herein provides unprecedented opportunities to create advanced bioanalytic and biosensor technologies.